A gendered analysis of goat ownership and marketing in Meru, Kenya - Waithanji, Elizabeth M.; Njuki, Jemimah; Mburu, S.; Kariuki, Juliet B.; Njeru, F. (Informa UK Limited, 2015)
Studies show that women are more likely to own small, rather than, large livestock. This study sought to establish gendered preference for different livestock species while focusing on the gendered differences in ownership, management, and marketing of goats in Meru, Kenya. Men demonstrated a higher preference for cattle than women, who had a higher preference for poultry than men. Men and women preferred goats equally, but women derived and managed more income from goats than men. Development projects should apply a gender lens before introducing different livestock species as gender differences exist in the preference and the management of different livestock.